The Development of a Character Education Evaluation Model Based on Authentic Assessment at PAM Pilot Elementary Schools in Makassar - Rosmiati, Rosmiati; Syahid, Akhmad; Nengsih, Ratika; Setiawati, Nur (TARBAWY: Indonesian Journal of Islamic Education, 2023)
This research aims to understand the development of an authentic assessment-based character education evaluation model to shape students' character, integrated through learning at the PAM Pilot Elementary School in Makassar. Apart from that, the research specifically examines character, sense of responsibility, honesty, caring, cooperation, politeness, self-confidence and discipline, in learning carried out in fifth grade students in Makassar. The specific target is to produce an authentic learning model to shape the character of elementary school students in Makassar City. This type of RD research and development research adheres to the model developed by Gall and Borg (1983). The ten steps are as follows. 1) introduction (literature review and initial survey), 2) design); 3) initial model development; 4) limited investigative tests; (5) revision of the initial model; (6) wider trials; (7) improvement of operational models; (8) field trials (feasibility); (9) revision of final production; (10) dissemination and implementation. The steps in development research as stated by Gall and Borg are indeed very complete, but it cannot be avoided that they can be implemented in the field according to capabilities and limitations of time and funding. The ten steps developed by Gall Borg were modified into three steps, namely: (1) introduction, (2) model design, (3) model development. This concept is used without negating the essence of research and development (RD). Data processing of information obtained shows that the authentic-based character education evaluation model with a behavioral approach meets the effectiveness criteria.